Perlindungan Hukum Terhadap Korban Ekspolitasi Seksual Komersial Anak (ESKA) Dalam Ranah Pariwisata - Saparudin Efendi; Prandy Arthayoga Louk Fanggi (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
This article raises the Indonesian government's efforts to reduce commercial sexual exploitation of children (CSEC) in the tourism industry. As a link in supporting the sustainable development agenda for the creation of a society that is earlier aware of sexual violence against children. CSEC will usually involve a lot of tourism actors, both foreign and domestic, who put children at a disadvantage physically and mentally. The purpose of this paper is to first look at the forms of CSEC in Indonesia and secondly, what strategic steps have been taken by Indonesia to prevent CSEC from occurring in the tourism sector. This research method includes normative research, which uses the doctrinal and theoretical principles in the science of law, regarding the legal materials used, which consist of primary legal materials, secondary legal materials, and tertiary legal materials. This method uses the norms that apply to the conceptual approach, namely referring to concepts, principles, and theories that are related to the issues discussed. as well as based on several programs that have been implemented by the government and are carried out with limited prevention by maximizing the role of the various parties who are responsible for preventing cases of CSEC. These steps are of course carried out in order to create a harmonious environment in the life of the nation and state, as well as to protect citizens from the threat of crime.